Strategi Indonesia dalam Menangani Kasus Illegal Fishing di Wilayah Perairan Natuna - Ririn Atifa Naila; Imam Fadhil Nugraha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Natuna waters are the most vulnerable area to illegal fishing because there is abundant potential for fishery resources. It was recorded that from May to December 2016, there were 280 foreign vessels in Natuna waters, which resulted in economic losses of 2.98 trillion Rupiah. This study aims to examine and assess the policies and actions that the Indonesian government has implemented in overcoming illegal fishing activities in the area. The results of this study are that the Natuna Waters Area is part of the Indonesian Archipelago Sea Lane (ALKI) and functions as a global waterway. The Natuna Waters Area borders with neighboring countries and is connected to open waters, making it vulnerable to illegal fishing activities. The Indonesian government's strategy in dealing with cases of unlawful fishing in Natuna waters effectively increases the protection of state sovereignty and marine resources through policies such as sinking ships and maritime diplomacy. However, this implementation policy overcomes obstacles in the form of intimidation from other countries, such as China, and weaknesses in supervision and coordination between domestic institutions, which can affect microorganisms in fisheries management and maritime security in the area.